2016
DOI: 10.1186/s13578-016-0099-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide decreases high glucose/palmitate-induced autophagy in endothelial cells by the Nrf2-ROS-AMPK signaling pathway

Abstract: BackgroundExcessive autophagy induced by extravagant oxidative stress is the main reason for diabetes-induced vascular endothelial cells dysfunction. Hydrogen sulfide (H2S) has anti-oxidative effects but its regulation on excessive autophagy of vascular endothelial cells is unclear.MethodsIn this study, aorta of db/db mice (28 weeks old) and rat aortic endothelial cells (RAECs) treated with 40 mM glucose and 500 μM palmitate acted as type II diabetic animal and cellular models, respectively, and 100 μMNaHS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 60 publications
(59 reference statements)
2
53
0
Order By: Relevance
“…For instance, embryonic stem cells present a fragmented mitochondrial morphology for their survival (40). Interestingly, several papers have shown that CBS or H 2 S is required for induction of autophagy, and thus, the targeting of CBS or elimination of H 2 S abrogates autophagy (41,42). In the absence of autophagy or damaged mitochondria, MFNs can be additionally targeted by E3 ubiquitin ligases, such as March V (43), HUWE1 (38), and Mdm30 (44).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, embryonic stem cells present a fragmented mitochondrial morphology for their survival (40). Interestingly, several papers have shown that CBS or H 2 S is required for induction of autophagy, and thus, the targeting of CBS or elimination of H 2 S abrogates autophagy (41,42). In the absence of autophagy or damaged mitochondria, MFNs can be additionally targeted by E3 ubiquitin ligases, such as March V (43), HUWE1 (38), and Mdm30 (44).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK inhibits diabetes-induced cardiomyocyte apoptosis and prevents cardiac dysfunction in diabetic animals after treatment with metformin [9], suggesting that further investigations are needed to explain the role of AMPK in the regulation of autophagy and apoptosis. Interestingly, our previous study demonstrated that H 2 S inhibits induction of protein synthesis in the endothelial cells after high glucose treatment by activation of AMPK [56]. Indeed, activation of AMPK inhibits mTOR, the negative regulator of autophagy, and subsequently stimulates autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous H2S protect arterial endothelial cells by suppressing excessive autophagy induced by oxidative stress through the Nrf2-ROSAMPK signaling pathway [53]. Myocardial fibrosis is the predominant pathological characteristic of diabetic myocardial damage.…”
Section: Autophagy and H2s Signalingmentioning
confidence: 99%